Theatre-based techniques for enhancing creativity in engineering education: An evaluation study of the creativity academy program - Hao He; Noah Glaser; Dana AlZoubi; K. Rende Mendoza; Heather K. Hunt; Suzanne Burgoyne (Springer, 2023)
Abstract In response to the underemphasis on creativity in college engineering education and the limited knowledge and skills of early-career engineering faculty to nurture students' creativity, the Creativity Academy was designed as a faculty development program. Using theatre-based approaches, the program aimed to train early-career engineering faculty members to incorporate creativity into their classrooms. Two research questions were addressed: how faculty incorporate creativity after participating in the Creativity Academy and how students perceive faculty integration of creativity into their classes. Interviews were conducted with ten early-career engineering faculty members who participated in the training, as well as focus group interviews with each faculty participant's students. Results indicated that faculty participants mastered at least two creativity-fostering exercises to apply in their teaching, revised their syllabi, and incorporated these exercises to engage students and develop their creativity. Students confirmed the changes in their professors' teaching practices and expressed excitement. The study concludes that providing more opportunities for engineering students to develop creativity is essential, and the implications of the findings are discussed with suggestions for future Creativity Academy programs.